A proline-to-histidine substitution at position 225 of human immunodeficiency virus type 1 (HIV-1) reverse transcriptase (RT) sensitizes HIV-1 RT to BHAP U-90152. - Pelemans, H; Esnouf, R; Parniak, M; Vandamme, A; De Clercq, E; Balzarini, J (1998)
Two mutant virus strains in which the novel P225H mutation appeared in a V106A reverse transcriptase (RT)-mutated genetic background upon treatment of human immunodeficiency virus type 1 (HIV-1) with quinoxaline S-2720 were isolated. Surprisingly, the addition of the P225H mutation to the V106A RT mutant genetic background resensitized the V106A RT mutant virus to the non-nucleoside RT inhibitor (NNRTI) BHAP U-90152, but not to other NNRTIs. Construction of both recombinant viruses and recombinant RTs containing the V106A, P225H and V106A+P225H mutations revealed that P225H was indeed responsible for the marked potentiation of the antiviral activity of BHAP against the P225H single-mutant virus and the V106A+P225H double-mutant virus when compared to wild-type and V106A single-mutant viruses, respectively. An explanation for the markedly increased sensitivity of the P225H mutant HIV-1 RT to BHAP and not to the other NNRTIs was provided by the unique features of the X-ray structure of the RT-BHAP complex.